The Role Of Islamic Propagation Society International (IPSI) And Its Implementation Of Interfaith Dialogue In Mosque Penang, Malaysia - Muhammad Yusuf Khalid; Panji Hidayat Mazhisham; Nur Husna Mohamad Hussain; Ahmad Najaa' Haji Mokhtar; Khairunneezam Mohd Noor; Muhamad Zaki Mustafa (Universiti Sains Islam Malaysia, 2024)
Abqari Vol. 6, 2015